Sulfur and nitrate synergistic removal material, preparation method and application

By developing a sulfur nitrate collaborative removal material, using the combination of CAO, NH4HCO3, long stone minerals and polymer carboxyl polymer to solve the problem of high sulfur prices in existing technology, and achieve efficient tail gas desulfurization and denitration denitration and denitrification. Effect is suitable for industrial promotion.

CN119327248APending Publication Date: 2025-01-21HANGZHOU ZHENGLONG ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411220451.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In the prior art, sodium bicarbonate has excellent performance as a desulfurizer, but its high price limits its wide application. Industrial enterprises urgently need to find alternatives to desulfurizers with reasonable prices and superior performance.

Method used

Develop a sulfur nitrate collaborative removal material. By mixing the CAO, NH4HCO3, long stone minerals and polymer carboxyl polymers in organic solvents, the ball is grinded by the ball occur.

Benefits of technology

It achieves efficient tail gas desulfurization and denitrification, increases the specific surface area and adsorption capacity of the desulfurizer, and reduces the SO2 and NOx concentrations in the tail gas. The preparation method is simple and suitable for industrial promotion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327248A_ABST
    Figure CN119327248A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur and nitrate synergistic removal material, a preparation method and application, and the preparation method of the sulfur and nitrate synergistic removal material comprises the following steps: uniformly mixing CaO, NH4HCO3, feldspar minerals and a high-molecular carboxyl polymer in an organic solvent, and carrying out ball milling to obtain a desulfurizer; the feldspar mineral is one or more of orthoclase, albite, anorthite, baryta feldspar, baryta ice feldspar, microcline feldspar and sandite; the organic solvent is one or more of ethanol, isopropanol, normal propyl alcohol and acetone; the high-molecular carboxyl polymer is one or more of vinyl acrylate copolymer, maleic acid copolymer, polyacrylic acid, polyethylene acid and polyamic acid polybutenoic acid. The preparation method of the synergistic sulfur and nitrate removal material is simple, all the materials are mixed and then subjected to ball milling to prepare high-homodisperse and small-particle-size desulfurizer pug, and then desulfurization and denitration of industrial tail gas can be achieved through a spraying device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sulfur-nitrate synergistic removal materials, and in particular to sulfur-nitrate synergistic removal materials, preparation methods and applications. Background Art

[0002] With the rapid development of industrialization, fossil fuels such as coal, oil and natural gas are widely used in energy production and chemical processes. However, these fossil fuels will produce a large amount of sulfur dioxide (SO2) emissions during combustion or processing, posing a serious threat to the environment and human health. Sulfur dioxide is one of the main sources of air pollution, causing environmental problems such as acid rain and haze, and also has negative effects on human health, such as respiratory diseases.

[0003] At present, in the field of industrial desulfurization, sodium bicarbonate (baking soda) is a widely used desulfurizer. Sodium bicarbonate has a good desulfurization effect, which is mainly attributed to its unique chemical properties and reaction mechanism. It can quickly react with sulfur dioxide (SO2) in flue gas to generate sodium sulfate (Na2SO4) and water (H2O), while releasing carbon dioxide (CO2). Under high temperature conditions, the gas released by the decomposition of sodium bicarbonate can increase its surface area, increase the contact area with sulfur dioxide and the reaction rate. The fineness of sodium bicarbonate has a direct impact on its desulfurization efficiency. The finer the powder, the more obvious the desulfurization effect. Although sodium bicarbonate has excellent desulfurization performance, its high price has become an obstacle to its further promotion. Factors such as raw material costs, complex production processes, and imbalance between market demand and supply have jointly pushed up the price of sodium bicarbonate desulfurizers. In order to reduce the cost of desulfurization, industrial enterprises are in urgent need of finding more reasonably priced desulfurizer substitutes. The substitutes need to have desulfurization performance equivalent to that of sodium bicarbonate to ensure that the environmental protection requirements of industrial production are met. While pursuing economic benefits, we also need to consider the environmental friendliness and sustainability of alternatives to reduce negative impacts on the environment.

[0004] In summary, although sodium bicarbonate has excellent performance as a desulfurizer, its high price limits its widespread application. Therefore, finding substitutes with comparable performance and reasonable prices has become an important research direction in the current industrial desulfurization field. As a potential substitute, highly active calcium-based desulfurizers are gradually attracting attention from the industry due to their low price, high desulfurization efficiency and easy handling. However, their specific surface area is low and they are prone to agglomeration, so it is necessary to consider increasing their specific surface area and preventing agglomeration.

[0005] Calcium-based desulfurizers first generate Ca(HCO3), and the main substance generated after absorbing sulfur dioxide is Ca(HSO3), which solidifies into CaSO4·2H2O after absorbing oxygen. However, its curing efficiency needs to be improved. The carboxyl functional groups and other possible polar groups (such as hydroxyl groups, amide groups, etc.) in high molecular carboxyl polymers can form hydrogen bonds or coordination bonds with SO2 molecules, thereby achieving strong adsorption of SO2. The long chain structure of high molecular polymers makes its surface area relatively large, which can provide more adsorption sites and further enhance its adsorption capacity. And it can be used as a buffer to lower the overall pH value, increase the oxidation rate and adsorption efficiency of SO2 to reduce the SO2 concentration in the exhaust gas.

[0006] In order to achieve the dual carbon goals, the Chinese government has introduced a series of policies, including promoting green and low-carbon transformation, adjusting and optimizing the industrial structure, and promoting energy transformation. These policies not only focus on reducing carbon emissions, but also emphasize improving energy efficiency and guiding low-carbon production and consumption. Given the important role of desulfurizers in reducing industrial sulfur dioxide emissions, their integration with dual carbon policies is crucial. The high price of sodium bicarbonate may hinder the widespread implementation of industrial desulfurization, which in turn affects the realization of dual carbon goals. Therefore, it is urgent to find a reasonably priced and high-performance desulfurizer substitute. The current industrial desulfurization field needs to find a reasonably priced, high-performance and environmentally sustainable desulfurizer substitute. This is not only the key to achieving widespread application of industrial desulfurization, but also one of the important measures to promote the realization of dual carbon goals.

[0007] Therefore, developing a new type of sulfur-nitrate synergistic removal material is the key to solving the above problems. Summary of the invention

[0008] Based on the technical problems existing in the background technology, the present invention proposes a desulfurization and denitrification sulfur-nitrate synergistic removal material, a preparation method and an application, which has good desulfurization and denitrification effects, and the preparation method is simple, which is conducive to industrial promotion and application.

[0009] The preparation method of the sulfur-nitrate synergistic removal material proposed by the invention comprises the following steps: mixing CaO, NH4HCO3, feldspar minerals and high molecular weight carboxyl polymer in an organic solvent, and obtaining a desulfurizing agent by ball milling.

[0010] Preferably, the feldspar mineral is one or more of orthoclase, albite, anorthite, barium feldspar, barium adularia, microcline and sanudite.

[0011] Preferably, the organic solvent is one or more of ethanol, isopropanol, n-propanol and acetone.

[0012] Preferably, the high molecular weight carboxyl polymer is one or more of vinyl acrylate copolymer, maleic acid copolymer, polyacrylic acid, polyvinyl acid, polyamic acid and polybutenoic acid.

[0013] Preferably, the mass ratio of CaO, NH4HCO3 and high molecular weight carboxyl polymer is 1:0.5-2:0.02-0.10; and the feldspar minerals account for 0.5-10wt% of the total mass of the sulfur-nitrate synergistic removal material.

[0014] Preferably, the ball milling conditions are: a rotation speed of 400-6000 r / min, first forward rotation for 5-20 min, stop for 20-60 s, then reverse rotation for 5-20 min, stop for 20-60 s, and cycle 2-4 times.

[0015] The present invention provides a sulfur-nitrate synergistic removal material prepared by the method mentioned above.

[0016] The present invention proposes the application of the above-mentioned sulfur-nitrate synergistic removal material in the desulfurization and denitrification of industrial tail gas.

[0017] Beneficial technical effects of the present invention:

[0018] (1) The sulfur-nitrate synergistic removal material of the present invention has a high tail gas desulfurization and denitrification efficiency. NH4HCO3 decomposes to generate gas, forms bubble channels on the surface of CaO, and together with the high molecular carboxylic acid polymer as a skeleton, increases the specific surface area of ​​the desulfurizer, thereby increasing its contact area with sulfur dioxide and increasing the desulfurization efficiency; the addition of feldspar minerals can prevent the desulfurizer from becoming caking.

[0019] (2) In the desulfurization process, the polymer carboxyl polymer of the sulfur-nitrate synergistic removal material of the present invention can be used as a buffer to lower the overall pH value, thereby increasing the oxidation rate and adsorption efficiency of SO2 and reducing the SO2 concentration in the tail gas; in the denitrification process, the NH3 generated by the decomposition of CaO and NH4HCO3 and the polymer carboxylic acid polymer act synergistically to increase the denitrification efficiency. The NH3 generated by the decomposition of NH4HCO3 and the carboxylate radical of the polymer carboxylic acid are the main reducing agents, directly participating in the NO x The CaCO3 generated by the decomposition of CaO and CO2 generated by NH4HCO3 is an effective sulfur-nitrate synergistic removal material in the denitration process, playing a catalytic role. In addition, the high molecular weight carboxylic acid polymer can also promote the reaction of NH3 and NO by adsorption, catalysis and as a reaction medium. x reaction, thereby improving the denitrification efficiency.

[0020] (3) The preparation method of the present invention is simple. It only requires mixing the materials and then ball-milling them to obtain a highly uniformly dispersed, small-particle desulfurizer sludge, and then the desulfurization and denitrification of industrial tail gas can be achieved through a spraying device. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a graph showing the agglomeration test results of the sulfur-nitrate synergistic removal material proposed in the present invention. DETAILED DESCRIPTION

[0022] The present invention will be further explained below in conjunction with specific embodiments.

[0023] Example 1

[0024] The preparation method of the sulfur-nitrate synergistic removal material proposed by the present invention comprises the following steps:

[0025] S1: Add 45g CaO powder into 100ml ethanol solution, stir until the powder becomes viscous, and stir for 1h to obtain mud A;

[0026] S2: Add 4 g of orthoclase to mud material A and stir at room temperature for 1 h to obtain mixed mud material B;

[0027] S3: Add 45g NH4HCO3 to the mixed mud B and stir at room temperature for 1h to obtain mixed mud C;

[0028] S4: adding 6 g of maleic acid copolymer to the mixed mud C, and stirring at room temperature for 1 hour to obtain mixed mud D;

[0029] S5: Add the mixed mud material D into the ball mill, rotate at a speed of 5400r / min, rotate forward for 10min, stop for 30s, reverse for 10min, stop for 30s, and repeat twice to obtain a uniformly dispersed sulfur-nitrate synergistic removal material mud material.

[0030] Example 2

[0031] The difference between this embodiment and embodiment 1 is that NH4HCO3 in S3 is changed to NaHCO3, and the other conditions are the same as those in embodiment 1.

[0032] Example 3

[0033] The difference between this embodiment and embodiment 1 is that the amount of CaO added in S1 is 30 g, the amount of NH4HCO3 added in S3 is 60 g, and the other conditions are the same as those in embodiment 1.

[0034] Example 4

[0035] The difference between this embodiment and embodiment 1 is that the amount of CaO added in S1 is 60 g, the amount of NH4HCO3 added in S3 is 30 g, and the other conditions are the same as those in embodiment 1.

[0036] Example 5

[0037] The difference between this embodiment and embodiment 1 is that the maleic acid copolymer in S4 is changed into a polyacrylic acid copolymer, and the other conditions are the same as those in embodiment 1.

[0038] Example 6

[0039] The difference between this comparative example and Example 1 is that the amount of CaO added in S1 is 46 g, the amount of orthoclase added in S2 is 2 g, and 45 g NH4HCO3 in S3 is changed to 46 g NH4HCO3. The other conditions are the same as those in Example 1.

[0040] Example 7

[0041] The difference between this comparative example and Example 1 is that the amount of CaO added in S1 is 43 g, the amount of orthoclase added in S2 is 8 g, and the 45 g NH4HCO3 in S3 is changed to 43 g NH4HCO3. The other conditions are the same as those in Example 1.

[0042] Comparative Example 1

[0043] The difference between this comparative example and Example 1 is that the 6 g of maleic acid copolymer in S4 is changed to 6 g of NH4HCO3, and the other conditions are the same as those in Example 1.

[0044] Comparative Example 2

[0045] The difference between this comparative example and Example 1 is that 45 g NH4HCO3 in S3 is changed to 45 g maleic acid copolymer, and the other conditions are the same as those in Example 1.

[0046] Comparative Example 3

[0047] The difference between this comparative example and Example 1 is that 4 g of orthoclase is not added to S2, and the other conditions are the same as those in Example 1.

[0048] The denitrification and desulfurization performances of the sulfur-nitrate synergistic removal materials prepared in Examples 1-5 and Comparative Examples 1-2 were tested. The test results are shown in Table 1.

[0049] The desulfurization test method is: the concentration of each gas (vol%) is controlled by a mass flow meter, SO2: 2000ppm, N2 is the balance gas, and the industrial tail gas is continuously introduced into the sulfur absorber for reaction. The reaction temperature is 30°C, the reaction pressure is 0.3MPa, and the mass space velocity of the industrial tail gas is 0.3h -1 , after 200 minutes, detect the sulfur dioxide flow at the outlet; the desulfurization efficiency calculation formula is η=(C1-C2) / C1×100%, where C1 is the concentration of SO2 at the inlet, C2 is the concentration of SO2 at the outlet, and it is obtained by testing with a flue gas analyzer.

[0050] The test method for denitrification is: the concentration of each gas (vol%) is controlled by a mass flow meter, NO: 2000ppm, N2 is the balance gas, and the industrial tail gas is continuously introduced into the nitrate absorber for reaction, the reaction temperature is 250°C, the reaction pressure is 0.3MPa, and the mass space velocity of the industrial tail gas is 0.3h -1 , after 200 minutes, detect NO at the outlet x The flow rate of denitrification efficiency is calculated by the formula η = (C3-C4) / C3×100%, where C3 is NO x The inlet concentration of C4 is NO x The outlet concentration is obtained by flue gas analysis test.

[0051] Table 1 Test results of desulfurization and denitrification performance of sulfur-nitrate synergistic removal materials

[0052]

[0053] It can be seen from the test results in Table 1 that the new high-efficiency sulfur-nitrate synergistic removal material of Example 1 of the present invention has the best desulfurization and denitrification efficiency. In the desulfurization process, NH4HCO3 decomposes to generate gas, and forms bubble channels on the surface of CaO, which together with the high molecular carboxylic acid polymer as a skeleton increase the specific surface area of ​​the desulfurizer, so that its contact area with sulfur dioxide increases, increasing the desulfurization efficiency, and the high molecular carboxyl polymer can be used as a buffer to lower the overall pH value, increase the oxidation rate and adsorption efficiency of SO2 to reduce the SO2 concentration in the tail gas. In the denitrification process, the NH3 generated by the decomposition of CaO and NH4HCO3 and the high molecular carboxylic acid polymer work synergistically to increase the denitrification efficiency. The NH3 generated by the decomposition of NH4HCO3 and the carboxylate of the high molecular carboxylic acid polymer are the main reducing agents, directly participating in NO x The CaCO3 generated by the decomposition of CaO and CO2 generated by NH4HCO3 is an effective sulfur-nitrate synergistic removal material in the denitration process, playing a catalytic role. In addition, the high molecular weight carboxylic acid polymer can also promote the reaction of NH3 and NO by adsorption, catalysis and as a reaction medium. x The reaction improves the denitration efficiency. According to the test results of Example 1 and Comparative Examples 1 and 2, it can be seen that NH4HCO3 and high molecular carboxylic acid polymer have a synergistic effect on improving the denitration performance of sulfur-nitrate synergistic removal materials.

[0054] The caking test was carried out on the sulfur-nitrate synergistic removal materials of Examples 1, 6, 7 and Comparative Example 3, and the results are as follows: Figure 1 As shown. Figure 1 It can be found from the data that the sulfur-nitrate synergistic removal material of the present invention has excellent anti-caking ability.

Claims

1. A method for preparing a sulfur-nitrate collaborative removal material, characterized in that: The method comprises the following steps: mixing CaO, NH4HCO3, feldspar minerals and high molecular weight carboxyl polymer in an organic solvent, and preparing a desulfurizing agent by ball milling.

2. The method for preparing the sulfur-nitrate synergistic removal material according to claim 1, characterized in that: The feldspar minerals include one or more of orthoclase, albite, anorthite, barium feldspar, barium adularia, microcline and sanudite.

3. The method for preparing the sulfur-nitrate synergistic removal material according to claim 1, characterized in that: The organic solvent is one or more of ethanol, isopropanol, n-propanol and acetone.

4. The method for preparing the sulfur-nitrate synergistic removal material according to claim 1, characterized in that: The high molecular weight carboxyl polymer is one or more of vinyl acrylate copolymer, maleic acid copolymer, polyacrylic acid, polyvinyl acid and polyamic acid polybutenoic acid.

5. The method for preparing the sulfur-nitrate synergistic removal material according to claim 1, characterized in that: The mass ratio of CaO, NH4HCO3 and high molecular carboxyl polymer is 1:0.5-2:0.02-0.10; the feldspar minerals account for 0.5-10wt% of the total mass of the sulfur-nitrate synergistic removal material.

6. The method for preparing the sulfur-nitrate synergistic removal material according to claim 1, characterized in that: The conditions for ball milling are: rotation speed 400-6000r / min, first forward rotation for 5-20min, stop for 20-60s, then reverse rotation for 5-20min, stop for 20-60s, and cycle 2-4 times.

7. The sulfur-nitrate synergistic removal material prepared by the method according to any one of claims 1 to 6.

8. Use of the sulfur-nitrate synergistic removal material as claimed in claim 7 in industrial tail gas desulfurization and denitrification.